Entrapment and release kinetics study of dyes from BSA microspheres forming a matrix and a reservoir system. Issue 44 (23rd October 2020) - Sharma, Kusha; Saady, Abed; Jacob, Avi; Porat, Ze'ev; Gedanken, Aharon
Abstract : Two kinds of Bovine Serum Albumin (BSA)-loaded microspheres were prepared in water-organic bilayer systems using ultrasonic irradiation. Abstract : Two kinds of Bovine Serum Albumin (BSA)-loaded microspheres were prepared in water-organic bilayer systems using ultrasonic irradiation. The first method included an aqueous solution of BSA and water-soluble dye together, mixed with dodecane, that upon sonication formed a matrix system where the dye is concentrated in the protein shell. The other system included an aqueous solution of BSA mixed with octanol-soluble dye that, upon sonication, formed a reservoir system in which the dye filled the inner volume of the microspheres. Each of these microspheres was prepared with two different dyes and their leaching profiles into pure solvents were studied using UV-vis spectrometry. Fast leaching was observed at the beginning for both systems, which levelled-off after a certain time. For the matrix system, an equilibrium state was obtained after 100–200 hours, whereas for the reservoir system, leaching occurred much faster, within 1–3 hours. Such systems can serve as models for drug delivery agents.